Parallel Combinatory Spread Spectrum Underwater Acoustic Communication Technology. Issue 3 (February 2019) - Han, Shuping; Zhou, Hangcheng; Liu, Jianbo
Abstract: In order to achieve stable and high-speed information transmission between underwater platforms, an underwater communication system based on parallel combinatorial mapping sequence spread spectrum is built. The stability, concealment, economy and engineering realization of the system are analyzed in depth. At last, the experiment of anechoic pool proves that the system can still maintain the stable transmission of information under the condition of low signal-to-noise ratio. Compared with direct spread spectrum communication, the system greatly improves the communication rate on the basis of maintaining the stability of communication.